Oxidative Coupling–Thionation of Amines Mediated by Iron-Based Imidazolium Salts for the Preparation of Thioamides - Gisbert, Patricia; Pastor, Isidro M. (Synthesis, 2018)
An efficient and selective multicomponent oxidative coupling, involving the use of two different amines, sodium phosphate, and elemental sulfur have been described for the preparation of thioamides, employing microwave irradiation. The use of an iron(III)-based imidazolium salt is essential as catalyst. Indeed, the iron-based catalyst is involved in the oxidative coupling of the two amines and in the subsequent C–S bond formation. The protocol is useful for a wide variety of primary benzylamines and alkylamines, as coupling partners. Thus, various electron-rich and electron-poor substituents in the aromatic rings and also fused piperidine derivatives, are suitable starting materials in this reaction. Some of the obtained products are important synthetic intermediates for natural products.
Keywords: imidazolium salt; ionic liquid; iron(III) catalyst; sulfur; thioamides